Morphological features of the seminiferous and cauda Epididymides epithelia of breeding zebu bulls with normal and decreased testicular consistency - Chacón, Jorge (1999)
The fine morphology of the testes and epididymes collected from breeding Zebu (Bos indicus) bulls with normal or decreased testicular consistency (TC) at clinical palpation was studied. The ultrastructure of testicles with a slight to moderate reduction in consistency showed more obvious, albeit slight, degenerative changes in the seminiferous epithelium, with cellular debris present in Sertoli cells, compared with control animals. Abnormalities in the condensation of the chromatin and acrosomes during spermiogenesis were also common findings in cases of decreased TC. The cauda epididymides of these bulls did not show clear morphological deviations compared with controls, although the macrophagic activity of the epithelium was more pronounced, and cell debris as well as foreign cells were apparent in the lumen. The morphological findings confirm the relationship between a decreased TC at clinical palpation and the lowered normality of the testicu lar parenchyma, thus supporting the value of palpating scrotal contents as part of the field andrological clinical evaluation of breeding Zebu bulls in the tropics